2021
DOI: 10.1101/2021.03.22.436457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Species-specific developmental timing dictates expansion of the avian wing skeletal pattern

Abstract: How development is timed between differently sized species is a fundamental question in biology. To address this problem, we compared wing development in the quail and the larger chick. We reveal that developmental timing is faster in the quail than in the chick, and is associated with pattern specification, proliferation, organiser duration, differentiation and apoptosis. However, developmental timing is independent of the growth rate, which is equivalent between both species, and therefore scales pattern to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 66 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Recent work also focused on scaling in wing patterning between differently sized avian species, including quail, chick, and turkey (Stainton and Towers, 2021). The authors compared wing pattern growth rates between quail and chick and found that quail limb developmental timing is accelerated by 12 hours compared to chick.…”
Section: Differences In Developmental Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work also focused on scaling in wing patterning between differently sized avian species, including quail, chick, and turkey (Stainton and Towers, 2021). The authors compared wing pattern growth rates between quail and chick and found that quail limb developmental timing is accelerated by 12 hours compared to chick.…”
Section: Differences In Developmental Timingmentioning
confidence: 99%
“…The authors compared wing pattern growth rates between quail and chick and found that quail limb developmental timing is accelerated by 12 hours compared to chick. Between 0-12 hours of observation, quail wing buds grew at a significantly faster rate than chick wings and had faster proximodistal specification (Stainton and Towers, 2021). In addition, they identified that retinoic acid (RA) is responsible for species-specific developmental timing and wing scaling patterns (Stainton and Towers, 2021).…”
Section: Differences In Developmental Timingmentioning
confidence: 99%